2022
DOI: 10.1038/s41598-022-09253-2
|View full text |Cite
|
Sign up to set email alerts
|

Justice sensitivity is undergirded by separate heritable motivations to be morally principled and opportunistic

Abstract: Injustice typically involves some people benefitting at the expense of others. An opportunist might then be selectively motivated to amend only the injustice that is harmful to them, while someone more principled would respond consistently regardless of whether they stand to gain or lose. Here, we disentangle such principled and opportunistic motives towards injustice. With a sample of 312 monozygotic- and 298 dizygotic twin pairs (N = 1220), we measured people’s propensity to perceive injustice as victims, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
5
1
Order By: Relevance
“…Whereas other researchers have found that all perspectives of justice sensitivity are relatively stable traits [ 13 , 29 , 30 ], the test–retest stability of the perpetrator sensitivity subscale in our study was relatively low in the UK. Further, we found that the correlations of perpetrator sensitivity with variables of the nomological network and sociodemographic variables were less similar across the UK and Germany than were the correlations of the other justice sensitivity perspectives.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Whereas other researchers have found that all perspectives of justice sensitivity are relatively stable traits [ 13 , 29 , 30 ], the test–retest stability of the perpetrator sensitivity subscale in our study was relatively low in the UK. Further, we found that the correlations of perpetrator sensitivity with variables of the nomological network and sociodemographic variables were less similar across the UK and Germany than were the correlations of the other justice sensitivity perspectives.…”
Section: Discussioncontrasting
confidence: 99%
“…Wang et al [ 29 ] analyzed data from twins and found that all justice sensitivity perspectives were moderately heritable. In another twin study, Eftedal and colleagues [ 30 ] identified two factors, called principled and opportunistic justice sensitivity, to be essentially heritable. Whereas principled justice sensitivity represents heightened sensitivity to injustice of victims, observers, beneficiaries, and perpetrators, opportunistic justice sensitivity refers to heightened sensitivity to seeing oneself as a victim and decreased sensitivity to seeing oneself as a perpetrator.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These techniques revealed, for example, that sensitivities to being the perpetrator, victim, beneficiary, and observer of injustice are undergirded by separate and heritable latent motivations to be morally principled and opportunistic (so that the worse one reacts to injustice to oneself, the less one reacts to injustice to others). Furthermore, the unique environments that increase moral opportunism tend to also increase SDO, while genetic substrates that increase moral opportunism also increase SDO and lower altruism and generalized trust (Eftedal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Intelligence, mental health, and personality are among the many important phenotypes largely unaffected by the shared environment, and so are sociopolitical traits such as social dominance orientation (SDO; Kleppestø et al, 2019) and justice sensitivity (Eftedal et al, 2022). Notable exceptions include educational attainment, and political conservatism (Willoughby et al, 2021) and authoritarianism (Eftedal et al, 2020), which often have shared-environmental variance components of at least 20%.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques revealed, for example, that sensitivities to being the perpetrator, victim, beneficiary, and observer of injustice are undergirded by separate and heritable latent motivations to be morally principled and opportunistic (so that the worse one reacts to injustice to oneself, the less one reacts to injustice to others). Furthermore, the unique environments that increase moral opportunism tend to also increase SDO, while genetic substrates that increase moral opportunism also increase SDO and lower altruism and generalized trust (Eftedal et al, 2022).…”
mentioning
confidence: 99%